2020
DOI: 10.3390/ijerph17041144
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Perceptions of the Usefulness of Technologies for Engaging in Physical Activity: Using Focus Groups to Explore Physical Literacy

Abstract: Insufficient physical activity (PA) levels observed among older adults remain extremely high and pose a danger to developing and maintaining their physical literacy (PL). Each person’s level of PL partly depends on their physical and cognitive skills, confidence level, and degree of motivation to practice PA daily. New technologies, such as exergames and wearable fitness trackers, may enable older adults to increase their PL, stimulating uptake and ongoing PA participation. Objective: This focus group study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…A physically literate person needs to have social capability to promote health and physical activity throughout their lifespan. Campelo and Katz [ 12 ] also showed that the social domain of physical literacy includes family interaction, peer interaction, and therapist/staff interaction, etc. Hence, having group exercises or adding social interactions to exercise programs might increase older adults’ interest in participating [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A physically literate person needs to have social capability to promote health and physical activity throughout their lifespan. Campelo and Katz [ 12 ] also showed that the social domain of physical literacy includes family interaction, peer interaction, and therapist/staff interaction, etc. Hence, having group exercises or adding social interactions to exercise programs might increase older adults’ interest in participating [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical literacy is “the motivation, confidence, physical competence, knowledge and understanding to value and take responsibility for engagement in physical activities for life” [ 6 ]. Physical literacy also refers to the integration of physical, perceptual, knowledge, cognitive, psychological, sociality, and behavioral capabilities, echoing the need for an active, healthy, and fulfilling lifestyle [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Physical literacy could protect older adults from chronic diseases and disability.…”
Section: Introductionmentioning
confidence: 99%
“…46 PA literacy can be a promising strategy for achieving lifelong participation in PA, and is a meaningful approach to reducing sedentary behaviors and preventing chronic diseases. 47 From the participants' point of view, the current general atmosphere of the community is not PA-friendly, and might not motivate people to perform PA. They believed that urbanization and mechanization can lead to laziness and increased sedentary behavior, through changing the patterns of work, transportation, entertainment, and consumption.…”
Section: Discussionmentioning
confidence: 99%
“…46 PA literacy can be a promising strategy for achieving lifelong participation in PA, and is a meaningful approach to reducing sedentary behaviors and preventing chronic diseases. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Older people face barriers to take part in exercise, but they identify positive aspects of strength and balance activities [ 16 , 17 ] and report positive perceptions about implementing technology to exercise [ 18 ]. Hence, appropriate programs and interventions based on education and training can help overcome the barriers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%